The Relationship Between Kinesiophobia and Mobilization of Patients with Brain Tumor Surgery - Emine Öner Karaveli; Sema Koçaşlı; Ercan Bal (KHD-Production, 2024)
This study investigated the relationship between kinesiophobia and mobilization levels of patients with brain tumor surgery. This descriptive and correlation study was conducted between April and October 2022. The sample consisted of 80 patients who had brain tumor surgery. Data were collected using a personal information form (PIF), the Tampa Scale of Kinesiophobia (TSK), the Patient Mobility Scale (PMS), and the Observer Mobility Scale (OMS). Participants had a significantly higher mean TSK score on day one after surgery than on days two, three, and four after surgery. Participants had significantly higher PMS scores on the day immediately following surgery compared to two, three, and four days after surgery. Furthermore, they had significantly higher OMS scores on the day immediately following surgery compared to two, three, and four days after surgery. Participants with a history of falls had significantly higher TSK, PMS and OMS scores on days one, two, three, and four after surgery compared to those without a history of falls (p<0.05). Similarly, participants who experienced a fear of falling during mobilization exhibited significantly higher TSK, PMS and OMS scores on days one, two, three, and four after surgery compared to those without such fear. There was a moderate positive correlation between TSK, PMS, and OMS scores on days one, two, three, and four after surgery. As a result of this study, nurses should be aware that they experience kinesiophobia when mobilizing patients after neurosurgery. Therefore, they should develop nursing care to prevent this fear from preventing them from moving. In addition, for patient safety, patient falls that may occur together with fear of movement must be handled carefully. It was determined that the mobilization levels of patients who underwent brain tumor surgery decreased as their fear of movement increased after surgery. As a result, it is important that nurses should take fall prevention measures to reduce patients' fear of movement, ensure that they do not move alone during their mobilization, and provide patient training to help them move more. Our findings have the potential to serve as a foundation for future research endeavors and offer practical solutions for nurses working in neurosurgery clinics.